Penyuluhan Kualitas Kemasan Produk dan Keamanan Pangan Kepada Pelaku UMKM dan Siswa SMK di Desa Tukak Kabupaten Bangka Selatan: Pengabdian - Rahmad Firdaus; Jenni Lambas Siregar; Sutiono; Junaidi Abdillah; Suhardi; Fithriawan Nugroho (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This community service activity aims to improve product packaging quality and enhance understanding of food safety among MSME actors and vocational high school students in Tukak Village, South Bangka Regency. The main problems faced by local MSMEs include the use of simple packaging that does not meet food safety standards and the limited understanding of hygienic production practices. The activity was carried out through lectures, interactive discussions, and hands-on practice involving 50 participants. The pre-test and post-test evaluations showed a significant increase in participants’ knowledge, rising from an average of 45% to 85%. In addition, technical skills such as selecting food-grade packaging materials, sealing techniques, sanitation and hygiene practices, and designing product labels also improved substantially. The attendance rate, participation, and enthusiasm of the participants demonstrated that the training methods implemented were effective and relevant to the needs of the MSMEs. This program contributed significantly to enhancing the competitiveness of local businesses while preparing vocational students as competent young entrepreneurs. The recommendations include the need for ongoing mentoring, improved access to quality packaging materials, and advanced training related to food product licensing.